HADIS TENTANG PENCIPTAAN PEREMPUAN (TINJAUAN HADIS TAḤLĪLĪ) - Nurkholidah Nurkholidah; Tami Dewi Puspa Rahayu (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2023)
This study is a contextual understanding of the hadith of the creation of women from ribs leading to the understanding that women are under the domination of men. This position causes women's movement and rights to be narrow and limited. This study aims to determine the understanding of the hadith with the questions: 1). What is the quality of the hadith of women created from men's ribs? 2). How should we understand the hadith of women created from men's ribs? This study is a descriptive literature study. This study found that the hadith of women created from men's ribs is a valid hadith both in terms of sanad and matan. The correct understanding of the hadith of women created from men's ribs is a contextual approach to language. The figurative meaning "like a rib" is a metaphor for someone who is stiff and stubborn, who if forced will break, but if left alone will be hard like bone. So it is not a matter of the factual creation of women from men's ribs. But rather a metaphorical allusion about the character of women/wives and their relationships with men/husbands in household life, often stiff, impatient, and easily angered. The hadith says that women were created from crooked ribs. If a man wants to straighten them, they will break.Penelitian ini adalah Pemahaman secara kontekstual terhadap hadis penciptaan perempuan dari tulang rusuk mengarah pada pemahaman bahwa perempuan berada di bawah dominasi lelaki. Posisi ini menyebabkan gerak dan hak-hak perempuan menjadi sempit dan terbatas. Penelitian ini bertujuan untuk mengetahui pemahaman hadis tersebut dengan pertanyaan:1).Bagaimana kualitas hadis wanita tercipta dari tulang rusuk laki-laki? 2). Bagaimana sebaiknya memahami hadis wanita tercipta dari tulang rusuk laki-laki?. Penelitian ini merupakan penelitian pustaka yang bersifat deskriftif. Penelitian ini menemukan bahwa hadis wanita tercipta dari tulang rusuk laki-laki merupakan hadis shahih baik secara sanad maupun matan. Pemahaman yang tepat terhadap hadist wanita tercipta dari tulang rusuk laki-laki adalah kontekstual pendektan bahasa Makna kiasan seperti tulang rusuk‖ adalah kiasan tentang seseorang yang kaku dan keras kepala,yang jika dipaksakan akan patah,tetapi jika dibiarkan akan keras seperti tulang. Jadi bukan soal penciptaan yang faktual perempuan dari tulang rusuk laki-laki. Melainkan kiasan metaforis tentang karakter perempuan/ istri dan relasinya lelaki /suami dalam kehidupan rumah tangga,seringkali kaku,tidak sabar,dan mudah marah. sabda hadis tersebut wanita tercipta dari tulang rusuk yang bengkok jika lelaki ingin meluruskan nya maka patah.